Paclitaxel induced peripheral neuropathy in vitro - Michalová, Zuzana; Szekiová, Eva; Dzurjašková, Zuzana; Vanický, Ivo (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):306